Circulating Cytokines and Histological Liver Damage in Chronic Hepatitis B Infection. (31st October 2013) - Poovorawan, Kittiyod; Tangkijvanich, Pisit; Chirathaworn, Chintana; Wisedopas, Naruemon; Treeprasertsuk, Sombat; Komolmit, Piyawat; Poovorawan, Yong
Abstract : Each phase of hepatitis B infection stimulates distinct viral kinetics and host immune responses resulting in liver damage and hepatic fibrosis. Our objective has been to correlate host inflammatory immune response including circulating Th1 and Th2 cytokines in patients with chronic hepatitis B infection with liver histopathology. Sixty-four patients with chronic hepatitis B without previous treatment were recruited. The liver histology and histological activity index were assessed for various degrees of necroinflammation and hepatic fibrosis. We determined circulating levels of the Th1 and Th2 cytokines. Forty-six males and 18 females at a median age of 34.5 years were studied. HBeAg was present in 28/64 (43.75%) of the patients. In patients negative for HBeAg, IL-10 and IFN-gamma were significantly correlated with degrees of necroinflammation (r = 0.34, r = 0.38, resp.;P < 0.05 ). Moreover, TNF-alpha was significantly correlated with degrees of fibrosis (r = 0.35 ;P < 0.05 ), and IL-10 and TNF-alpha were significantly correlated with significant fibrosis (r = 0.39, r = 0.35, resp.;P < 0.05 ). These correlations were found in the HBeAg negative group as opposed to the HBeAg positive group. In HBeAg negative patients, circulating cytokines IL-10 and IFN-gamma were correlated with degrees of necroinflammation, whereas IL-10 and TNF-alpha were correlated with significant fibrosis.